Simulasi Era Disrupsi dalam Iklan Apple “Crush” - Budhiman, Arief; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Technological progress is something that has a significant aspect of human life, one example is social media. Companies use these media to share messages with audiences. Every advertisement has a message meaning, either implicit or explicit, that it wants to convey to the audience and each audience has a different view in understanding the meaning contained in the advertisement. To find out the implied meaning in a message, help from semiotics is needed. One company that conveys interesting implied messages in advertising is Apple, which conveys the theme of change. Researchers want to examine further the meaning of the implied messages in the elements contained in the iPad Pro advertisement by carrying out semiotic analysis according to Roland Barthes through the meaning of connotation and meaning of denotation, disruption theory which discusses how change changes the order of human life, as well as assistance from the internet to strengthen the data needed to support the results of this research. Through the method used in this research, there are forms of digital representation in the Apple iPad Pro advertisement with the title